Tailoring of Multisource Deposition Conditions towards Required Chemical Composition of Thin Films - Gutwirth, Jan; Kotrla, Magdaléna; Halenkovič, Tomáš; Nazabal, Virginie; Němec, Petr (Nanomaterials (Basel, Switzerland), 2022)
The model to tailor the required chemical composition of thin films fabricated via multisource deposition, exploiting basic physicochemical constants of source materials, is developed. The model is experimentally verified for the two-source depositions of chalcogenide thin films from Ga-Sb-Te system (tie-lines GaSb-GaTe and GaSb-Te). The thin films are deposited by radiofrequency magnetron sputtering using GaSb, GaTe, and Te targets. Prepared thin films are characterized by means of energy dispersive X-ray analysis coupled with a scanning electron microscope to determine the chemical composition and by variable angle spectroscopic ellipsometry to establish film thickness. Good agreement between results of calculations and experimentally determined compositions of the co-deposited thin films is achieved for both the above-mentioned tie-lines. Moreover, in spite of all the applied simplifications, the proposed model is robust to be generally used for studies where the influence of thin film composition on their properties is investigated.
Keywords: co-sputtering; model; thin film; Ga–Sb–Te; deposition; calculation; sputtering